On the recall of a mayor in Republika Srpska - Marković Goran (Zbornik Radova Pravnog Fakulteta u Nišu, 2023)
In this paper, the author analyzes the institution of recall of a mayor in the legal system of the Republika Srpska by critically examining the provisions of two legislative acts: The Election Act of Republika Srpska and the Local Self-government Act of Republika Srpska. The institution of recall has a serious democratic potential because it is an instrument enabling political control of mayors by citizens. However, the current legal solutions in Republika Srpska limit this potential because they do not encourage citizens to use this instrument of political control, which is not the case with political parties. Given the fact that the decision on initiating the recall procedure depends on a local assembly, recall has very often been used as a tool for political confrontation between a local assembly and a mayor, while the citizens have remained a second-class political subject. The Election Act of Republika Srpska does not contain adequate provisions on the protection of rights of citizens and political subjects during the recall procedure. In fact, this issue is relatively unregulated or underregulated. The Local Self-government Act of Republika Srpska protects a local assembly which triggers an unsuccessful recall procedure since there is no legal guarantee that such a local assembly would be dissolved. The author proposes different solutions which should improve the regulation of this legal institute and reduce the possibility of turning it into a tool for political manipulation.